Pengaturan Perlindungan Hukum Bagi Wanita Gangguan Jiwa Yang Menjadi Korban Tindak Pidana Kesusilaan - Rasyid, M. Akbarizan; Ardiyanto, Syaifullah Yophi; Elmayanti, Elmayanti (Jurnal Ilmiah Wahana Pendidikan, 2024)
As a state of law, Indonesia upholds respect for human rights. In Indonesia, there are many people with mental disorders whose rights are not fulfilled, such as the right to be placed in health facilities, so that they end up being neglected and are vulnerable to becoming victims of criminal acts of rape due to the absence of supervision and when this happens the existing regulations have not provided maximum protection both from the perspective of material and formal criminal law. So that the formulation of the problem in this study is how the arrangement of legal protection for women with mental disorders who are victims of criminal acts of decency now, and how the arrangement of legal protection for women with mental disorders who are victims of criminal acts of decency in the future. The purpose of this research is to find out the current arrangements and formulate ideal regulations in the future. This type of research is classified into the type of research is normative legal research or can also be called doctrinal legal research. Normative legal research is library legal research. This research is included in normative juridical research, which is based on legal principles, especially those related to the principle of justice. From the results of the research, it can be concluded that related to legal protection for women with mental disorders who are victims of criminal acts of decency, there are regulations in Indonesian regulations, namely in the Criminal Code, the Sexual Violence Act, the Health Act, and the Mental Health Act. It is found that in the Criminal Code there are provisions that have the potential to hamper law enforcement on criminal acts of decency committed against women with mental disorders, in the TPKS Law the regulation regarding the rights of victims of criminal acts of decency is in accordance with the rights guaranteed in the United Nations Declaration Number 40/A/Res/34 of 1985. However, there are still problems and there needs to be criminal law reform in the future related to this matter. The author suggests that some substantial changes be made to the regulation of legal protection for women with mental disorders who are victims of criminal acts of decency as follows: reduction of the elements of the offence that must be proven in the article on the crime of rape against women with mental disorders, aggravation of the crime of rape committed against women with mental disorders, and renewal in terms of proof of criminal acts of decency committed against women with mental disorders.